APLIKASI TEKNOLOGI PANGAN DALAM PENGOLAHAN POTENSI LOKAL UMBI-UMBIAN DI DESA TAMANREJO KECAMATAN LIMBANGAN - Mudzanatun Mudzanatun; Khusnul Fajriyah; Iffah Muflihati (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2019)
Abstract. Processing of tubers as an abundant food ingredient in Tamanrejo Village which has not maximally processed brings problems that has resulted in a lack of partner income. Some of the factors that contributed to this problem included limited marketing areas, lack of product quality, and lack of entrepreneurial skills. The solution is given to answer partner problems in the form of application of food technology in the processing of tubers, business management, and marketing economics. The program of service activities is carried out in four stages, namely a) Identifying the problem; b) Program socialization; c) Extension and Training Program; and d) Monitoring and Evaluation. Activities carried out with farmer groups of women kelompok wanita tani/(KWT) " Lestari dan Family" namely: a) Dissemination of activity programs; b) Training and assistance in the processing of tubers into flour, various flavors of chips, donuts, purple dumplings, tela sticks; c) Online marketing training and mentoring; d) Building a marketing network by cooperating with stores, souvenir centers; e) Training of financial accounting; and f) monitoring and evaluating each stage of activity. The results obtained after this activity were the achievement of improved product quality and increased partner income.Keywords: Technology, processing, tubersAbstrak. Pengolahan umbi-umbian sebagai bahan pangan berlimpah di Desa Tamanrejo yang belum maksimal membawa permasalahan yang berdampak pada kurangnya pendapatan mitra. Beberapa faktor yang ikut berkontribusi dalam masalah ini antara lain keterbatasan area pemasaran, kurangnya kualitas produk, dan kurangnya keterampilan berwira usaha. Solusi yang diberikan untuk menjawab permasalahan mitra berupa penerapan teknologi pangan pada proses pengolahan umbi-umbian, manajemen usaha, dan ekonomi pemasaran. Program kegiatan pengabdian dilaksanakan dalam empat tahapan, yakni a) Indentifikasi masalah; b) Sosialisasi program; c) Program Penyuluhan dan Pelatihan; dan d) Monitoring dan Evaluasi. Kegiatan yang dilaksanakan dengan kelompok wanita tani (KWT) “Lestari dan Familiy” yakni: a) Sosialisasi program kegiatan; b) Pelatihan dan pendampingan proses pengolahan umbi-umbian menjadi tepung, ceriping aneka rasa, donat, onde-onde ungu, stik tela; c) Pelatihan dan pendampingan pemasaran online; d) Membangun jaringan pemasaran dengan cara bekerja sama dengan toko, pusat oleh-oleh; e) Melatih melakukan pembukuan keuangan; dan f) monitoring dan evaluasi setiap tahapan kegiatan. Hasil yang diperoleh setelah kegiatan ini adalah tercapainya peningkatan kualitas produk dan peningkatan pendapatan mitra.Kata Kunci: Teknologi, pengolahan, umbi-umbian.